Brain-Derived Neurotrophic Factor-Mediated Neuroprotection in Glaucoma: A Review of Current State of the Art - Lambuk, Lidawani; Mohd Lazaldin, Mohd Aizuddin; Ahmad, Suhana; Iezhitsa, Igor; Agarwal, Renu; Uskoković, Vuk; Mohamud, Rohimah (Frontiers in Pharmacology, 2022)
Retinal ganglion cells (RGCs) are neurons of the visual system that are responsible for transmitting signals from the retina to the brain via the optic nerve. Glaucoma is an optic neuropathy characterized by apoptotic loss of RGCs and degeneration of optic nerve fibers. Risk factors such as elevated intraocular pressure and vascular dysregulation trigger the injury that culminates in RGC apoptosis. In the event of injury, the survival of RGCs is facilitated by neurotrophic factors (NTFs), the most widely studied of which is brain-derived neurotrophic factor (BDNF). Its production is regulated locally in the retina, but transport of BDNF retrogradely from the brain to retina is also crucial. Not only that the interruption of this retrograde transport has been detected in the early stages of glaucoma, but significantly low levels of BDNF have also been detected in the sera and ocular fluids of glaucoma patients, supporting the notion that neurotrophic deprivation is a likely mechanism of glaucomatous optic neuropathy. Moreover, exogenous NTF including BDNF administration was shown reduce neuronal loss in animal models of various neurodegenerative diseases, indicating the possibility that exogenous BDNF may be a treatment option in glaucoma. Current literature provides an extensive insight not only into the sources, transport, and target sites of BDNF but also the intracellular signaling pathways, other pathways that influence BDNF signaling and a wide range of its functions. In this review, the authors discuss the neuroprotective role of BDNF in promoting the survival of RGCs and its possible application as a therapeutic tool to meet the challenges in glaucoma management. We also highlight the possibility of using BDNF as a biomarker in neurodegenerative disease such as glaucoma. Further we discuss the challenges and future strategies to explore the utility of BDNF in the management of glaucoma.